Hydrogen solubility in biphasic liquid reaction mixture of cinnamaldehyde hydrogenation: experimental and mathematical modeling study - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Journal of Chemical Sciences, 2022)
The solubility of hydrogen in the biphasic reaction mixture of cinnamaldehyde hydrogenation at 298 to 353 K has been determined in this work experimentally and by using a thermodynamic model. It is evident from many studies that the addition of extra phase, aqueous KOH as the fourth phase, to the three-phase cinnamaldehyde hydrogenation mixture [gas (hydrogen)-liquid (cinnamaldehyde + toluene)-solid (catalyst)] leads to enhancement of cinnamyl alcohol selectivity to a great extent. Determination of hydrogen solubility in this biphasic (organic-aqueous) reaction mixture is crucial to understand the intrinsic reaction kinetics of this reaction. The solubility of hydrogen was experimentally determined using a pressure drop method and reported in terms of Henry's constant. Firstly, hydrogen solubility was determined in pure components viz. toluene, cinnamaldehyde, and water followed by determination of its solubility in the cinnamaldehyde-toluene mixture, aqueous KOH, and eventually, in the reaction mixture containing the two immiscible liquid phases. The effect of changing concentrations in these mixtures and changing phase holdups in the total reaction mixture on hydrogen solubility was studied. Starting from pure components to the reaction mixture, the hydrogen solubility was predicted using a two-step thermodynamic approach involving regular solution theory and the theory of corresponding states. The solubility predictions from this thermodynamic model will be helpful in the accurate estimation of kinetic parameters.
Keywords: biphasic liquid mixture; gas-liquid-liquid-solid [GLLS]; hydrogen solubility; Hydrogenation; thermodynamic model

Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.